How does career-related parental support benefit career adaptability of medical imaging technology students in Asia-Pacific LMICs? The roles of psychological capital and career values - Zhang, Xiaohui; Shen, Yangjing; Xu, Junxiang; Cui, Guanyu (Frontiers in Psychology, 2025)
BackgroundChina, as a low- and middle-income country (LMIC) in the Asia-Pacific region, is advancing its rural medical and health system. Students of Medical Imaging Technology (MIT) in China, who will probably be employed in rural, are facing the pressure from both study and employment. Previous results proposed that career-related parent support and psychological capital could positively influence the level of career adaptability, while career-related parent support affects career values. This study aimed to explore the impact of career-related parental support on career adaptability and the mechanism between them, as well as the role of psychological capital and career values.MethodsA total of 520 (80.8% female) participants were recruited from MIT students in China, using Questionnaires about career-related parental support, psychological capital, career values, career adaptability. Path analysis was conducted using Mplus 8.3.ResultsThere was a significant correlation between career adaptability and career-related parental support, psychological capital and career values. Career-related parental support could positively predict students’ career adaptation. Psychological capital and career values played a parallel mediating role between career-related parental support and career adaptation.ConclusionThe results demonstrate that it is necessary to enhance career-related parental support to improve MIT students’ career adaptability by the enrichment of psychological capital and the refinement of career values, on the basis of the popularization of medical career programs among the public and medical literacy courses in colleges.